Behavioral Responses of Sea Lamprey to Varying Application Rates of a Synthesized Pheromone in Diverse Trapping Scenarios - Johnson, Nicholas S.; Lewandoski, Sean A.; Alger, Bethany J.; O’Connor, Lisa; Bravener, Gale; Hrodey, Peter; Huerta, Belinda; Barber, Jessica; Li, Weiming; Wagner, C. Michael; Siefkes, Michael J. (Journal of Chemical Ecology, 2020)
Use of the first fish pheromone biopesticide, 3-keto petromyzonol sulfate (3kPZS) in sea lamprey (Petromyzon marinus) control requires an understanding of both how the amount 3kPZS applied to a trap relates to catch, and how that relationship varies among stream types. By conducting 3kPZS dose-response experiments over two years and across six varied trapping contexts, we conclude (1) that 3kPZS application is best standardized by how much is emitted from the trap instead of the fully mixed concentration achieved downstream, and (2) that 3kPZS is more effective in wide streams (>30 m). In wide streams, emission of 3kPZS at 50 mg hr.−1 from the trap increased capture rate by 10–15% as sea lamprey were 25–50% more likely to enter the trap after encounter. However, in narrow streams (< 15 m), 50 mg hr.−1 3kPZS generally reduced probabilities of upstream movement, trap encounter, and entrance. While 3kPZS significantly influenced upstream movement, encounter, and capture probabilities, these behaviors were also highly influenced by water temperature, stream width, sea lamprey length, and sex. This study highlights that a pheromone component in a stream environment does not ubiquitously increase trap catch in all contexts, but that where, how, and when the pheromone is applied has major impacts on whether it benefits or hinders trapping efforts.
Keywords: Application rate; Invasive species; Lamprey; Pheromone; Trap; dept.che; peer-reviewed

Computational study in a PUI using XSEDE resources and ECSS support - Wang, Emily Z; Wang, Yigui (Association for Computing Machinery, 2020)
In the past 5 years, we have been using XSEDE resources and ECSS support to conduct research at Southern Connecticut State University (SCSU), a primary undergraduate institution (PUI). First, the regioselectivity was successfully investigated in the synthesis of 5-FU derivatives with phase transition method and silver salt method; then the Hard and Soft Acids and Bases (HSAB) principle and the Marcus theory were unified in the study of ambident reactivity; at last our research was expanded from reactions of molecules to reactions on the solid surface. We would like to share our results and emphasize the importance of XSEDE resources and ECSS support for the research in PUIs. © 2020 ACM.
Keywords: Computation theory; Computational research; Computational studies; ECSS; Marcus theory; Regioselectivity; Silver halides; Silver salts; Solid surface; Surface reactions; Synthesis (chemical); Undergraduate institutions; XSEDE; dept.che; primary undergraduate institution (PUI)

Using continuous student feedback to course-correct during COVID-19 for a nonmajors chemistry course - Hwang, Candy S. (Journal of Chemical Education, 2020)
The two major impetuses to improve STEM education are the shift to online learning and increasing active learning and engagement. Although the COVID-19 pandemic necessitated a rapid shift to online learning, this shift came at the cost of losing on-ground active learning strategies. This study provides descriptive analytical information on the impact of COVID-19 as it relates to student engagement, attendance, and viewership of video-recorded lectures for a nonmajors chemistry course. After the shift online, lecture video views significantly increased and weekly attendance significantly decreased. Prior to the pandemic, on-ground engagement via an active learning activity (i.e., Plickers) was significantly associated with on-ground achievement (i.e., exam 1). However, no significant association was found between online engagement (i.e., written responses/feedback submitted via a learning management system, referred to as LMS student feedback) and online achievement (i.e., final exam), potentially because the engagement resembled a formative assessment more than an active learning activity. Nonetheless, there was tremendous value in soliciting LMS student feedback for directing the course. Throughout the online period, there was an average of 112 responses per assignment, for a total of 1,344 responses, representing roughly a third of the students. Finally, analyses revealed no significant association of on-ground and online engagement, which suggests a different subset of students engaged while on-ground vs online. Instructors should highly consider soliciting weekly feedback through low-stakes assignments to gauge student learning and improve their courses while online. Copyright © 2020 American Chemical Society and Division of Chemical Education, Inc.
Keywords: Distance Learning/Self Instruction; First-Year Undergraduate/General; Internet Web-Based Learning; Nonmajor Courses; dept.che; peer-reviewed